Eloise at the wedding - McNamara, Margaret; Lyon, Tammie (New York : Aladdin Paperbacks, 2005)
Although she hasn$1 (Bt been invited to the wedding being held in the Plaza Hotel where she lives, Eloise finds a way to play an important role in the ceremony.s
Keywords: Plaza Hotel (New York, N.Y.) -- Fiction; Weddings -- Fiction; Hotels, motels, etc. -- Fiction; Humorous stories; New York (N.Y.) -- Fiction